2009
DOI: 10.1055/s-0029-1211078
|View full text |Cite
|
Sign up to set email alerts
|

Radioiodine Treatment of Basedow's Disease: Interference and Influence Factors, Risk Estimation

Abstract: I-131 treatment of Basedow's disease is effective and safe. Relatively high energy doses to the thyroid in the range of 150-200 Gray are needed in endemic goiter areas, where immunogenic hyperthyroidism may coincide with functional autonomy. Induction of euthyroidism by low doses of antithyroid drugs (methimazole, carbimazole) before I-131 treatment prevents complications and has no significant influence on outcome of I-131 therapy. As compared to alternative therapeutic modalities, the risks of I-131 are low.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2013
2013
2013
2013

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(2 citation statements)
references
References 18 publications
0
1
0
1
Order By: Relevance
“…The authors suggested that hypometabolism, due to the hypothyroidism induced by PTU, could be the mechanism of such radioprotection (24). Some authors reported a radioprotective effect of antithyroid compounds in patients undergoing radioiodine treatment, although the effect could be related to a reduction of intrathyroid iodine half life due to a direct inhibition of thyroperoxidase (25)(26)(27). Also, a possible interaction of MMI with the sodium iodide symporter may not be ruled out.…”
Section: Discussionmentioning
confidence: 99%
“…The authors suggested that hypometabolism, due to the hypothyroidism induced by PTU, could be the mechanism of such radioprotection (24). Some authors reported a radioprotective effect of antithyroid compounds in patients undergoing radioiodine treatment, although the effect could be related to a reduction of intrathyroid iodine half life due to a direct inhibition of thyroperoxidase (25)(26)(27). Also, a possible interaction of MMI with the sodium iodide symporter may not be ruled out.…”
Section: Discussionmentioning
confidence: 99%
“…Allerdings sind in der Literatur auch gegenteilige Beobachtungen vermerkt (Allahabadia et al 2001;Pfeilschifter et al 1997;Vogt et al 2006). (Peters et al 1995;Reiners 1991;Sabri et al 1999) Der Verlauf der TSH-Rezeptorautoantikörper in den ersten 6 Monaten nach RIT zeigte in der vorliegenden Arbeit ein aus der Literatur gut bekanntes Phänomen.…”
Section: Zahlreiche Studie Belegen Keine Einflussnahme Der Prätherape...unclassified